Las TIC en la calidad de servicio ofrecida por los profesores para el desarrollo de competencias de los alumnos universitarios (Revista Científica Compendium, 2018)
For any organization, the product and/ or service quality is a relevant value in order to be successful. However, despite the great efforts made by decision makers and employees within the organizations, it is not easy to achieve quality goals due to the economic, social and cultural challenges they must face in the competitive environment. Furthermore, quality is a concept that has been long discussed both in theory and practice. Universities can be considered as the most important service organizations. This is because of their impact on the society goes beyond that of any other organization, since the quality level of the education services offered by a university may, in turn, have an impact on the product and/or service quality of the organizations for which university trains professionals. Thus, leaders of universities must be aware of the responsibility they face in the process of training (in all aspects) future professionals. This is a task in which teachers are the main doers. In recent years, the information and communication technologies (ICT) have changed radically the way people work, communicate, live and do anything. Nowadays, the use of ICT offers countless advantages and opportunities. Accordingly, as education services may serve as a tool for the development of competences in students, this work is aimed at conducting a theoretical review of the impact that ICT have had on the quality of the education services provided by university teachers. Likewise, as a way for future research, this work will present a proposal to perform a quantitative measurement of such impact.
Keywords: quality, quality of service, ICT competences, Servqual, Caltic